Natural compounds targeting cellular redox homeostasis in malignancies: Natural compounds modulating cancer cell redox balance - Li, Xue; Li, Dan (Cellular and Molecular Biology, 2023)
Malignant tumors are one of the diseases that are most threatening to the health of people and their life. Moreover, it has already had a great impact on social and financial problems. With the further development of science and technology, the therapeutic approaches to malignant tumors are becoming more and more effective. At present, the common therapies for malignant tumors include surgical resections, radiotherapy, targeted therapy, and immunotherapy, which contribute to effectively suppressing tumor progression. However, these treatments showed severe side effects and complications. Over the last few decades, clinicians and researchers have found that chemical compounds extracted from natural products may be useful for treating cancer. Natural compounds like paclitaxel, doxorubicin, and camptothecin, have been successfully used to treat lung cancer as chemotherapeutic medicine. Numerous new natural compounds have been discovered that can be used to treat malignant tumors. As we know, the reactive oxygen species (ROS) closely connect to the occurrence, development, and apoptosis of tumors. The concentration of ROS in tumor cells plays an important role in the growth and development of tumors. In this review, we present a summary of some natural compounds that modulate redox homeostasis. They are promising candidates for the treatment option for cancer. Moreover, we have also explained the mechanism of the pharmacological reactions of natural compounds affiliated with ROS. It is hoped that new solutions can be provided for drug treatment of tumors.